Introducing Lisrel a guide for the uninitiated - Diamantopoulos, A. (Introducing statistical methods., 2000)
Introducing Lisrel provides a comprehensive introduction to Lisrel for structural equation modeling using a non-technical user-friendly approach. It shows the major steps associated with the formulation and testing of a model.